Trip Attraction Model at Elementary Schools in Suradita Valley Cisauk District Tangerang Municipal 2022 - Safira Sulisiani; Verdy Ananda Upa; Nur Hakim (Politeknik Negeri Jakarta, 2024)
Activity in schools area located in the Suradita Village area has the potential to cause traffic congestion because the schools start time coincides with the rush hour for work. This is due to the fact that the schools do not have a designated area for dropping off passengers, which forces vehicles transporting students to stop or park on the road, reducing the road’s capacity. The purpose of this research to determine trip attraction model, totals of trip attraction, factors that influence of trip attraction, and trip rate on SDN Rahayu, SDN Suradita, MIS Nurul Falah area. The research method used is interview to students, teachers, and staffs about trip data, also secondary data collection were amount of students, teachers, and staffs, land area, floor space, amount of classrooms, parking area of SDN Rahayu, SDN Suradita, MIS Nurul Falah area. Data that has been collected then analyzed with multiple linear regression method used SPSS 25.0 application with significant level 95%. Trip attraction model of SDN Rahayu, Suradita, and MIS Nurul Falah can be attained YSMDS = 0,998 + 0,199 JS + 0,067 JGK – 0,071 JRK with R2 (R square) = 0,636. Total of trip attraction that is generated by SDN Rahayu, SDN Suradita, MIS Nurul Falah area = 463 trip attraction/day. Based on t Test with significant level <0,05, therefore an influential factors are amount of students, teachers, and staffs, also amount of classrooms. Trip rate of SDN Rahayu, SDN Suradita, and MIS Nurul Falah = 0,9 people/m2 or 9 people/100m2.